2021
DOI: 10.1021/acs.iecr.1c02361
|View full text |Cite
|
Sign up to set email alerts
|

Alkaline Resins Enhancing Li+/H+ Ion Exchange for Lithium Recovery from Brines Using Granular Titanium-Type Lithium Ion-Sieves

Abstract: The mechanism of lithium ion-sieve adsorbing Li+ ions from brines is based on the Li+/H+ ion exchange, where Li+ ions in brines are adsorbed on ion-sieves to displace H+ ions, and the displaced H+ ions are released in brines in turn. If the released H+ ions are accumulated in brines, then brines become acidic, not conducive to Li+ ions adsorption on ion-sieves. Therefore, it is important to regulate the pH value in brines to be more than 7 during the lithium recovery from brines using ion-sieves. Instead of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 63 publications
0
22
0
Order By: Relevance
“…[62,151] Granulated adsorbents of calcinated Li 2 TiO 3 and polyvinyl butyral (PVB) were recently reported by Zhang et al reaching values of 25 mg Li g −1 from 200 mg Li L −1 LiOH solutions. [66,69] Lower adsorption values were also found when working with brines and the trend of higher adsorption in case of higher pH values, highlighted by Ooi et al [122] for LMO adsorbents, was confirmed for LTO adsorbents too. [59,60] Granulated adsorbents with either PVC or agar as binders were also tested in geothermal waters at higher temperatures.…”
Section: Lto-type Lismentioning
confidence: 76%
See 2 more Smart Citations
“…[62,151] Granulated adsorbents of calcinated Li 2 TiO 3 and polyvinyl butyral (PVB) were recently reported by Zhang et al reaching values of 25 mg Li g −1 from 200 mg Li L −1 LiOH solutions. [66,69] Lower adsorption values were also found when working with brines and the trend of higher adsorption in case of higher pH values, highlighted by Ooi et al [122] for LMO adsorbents, was confirmed for LTO adsorbents too. [59,60] Granulated adsorbents with either PVC or agar as binders were also tested in geothermal waters at higher temperatures.…”
Section: Lto-type Lismentioning
confidence: 76%
“…So far, no standard protocol to measure the selectivity of a process nor its recovery efficiency has been adopted. Several equa- Solid state Calcination [ 52,87,124,[227][228][229]238,239,257,258,282] Microwave combustion [48] Soft chemical Hydrothermal [71] Sol-gel [75] 𝛽-MnO 2 (Li 4 Mn 5 O 12 ) Solid state Calcination [55] Soft chemical Hydrothermal [50,53,129] H 1,6 Mn 1,6 O 4 Solid state Calcination [88,94] Soft chemical Hydrothermal [ 90,95,96] Sol-gel [74] H 1,33 Mn 1,67 O 4 Solid state Calcination [51,54,56,81,86,91] Soft chemical Hydrothermal [73] LTO H 2 TiO 3 layered [121,146] Solid state Calcination [57][58][59][60]62,63,[65][66][67]69,77,84,89] Soft chemical Hydrothermal…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…In the last 20 years, research efforts have been put for the development of novel processes for the recovery of lithium from low-grade and unfavorable deposits as for lithium end-life waste batteries, wastewaters from oil and gas fields, and low-lithium-content brines/bitterns. Although Li + content in bitterns is lower than that in salty brines reserves, as it reaches values from 2–3 ppm up to 20 ppm in Egyptian bitterns, saltwork bitterns are generated every year starting from seawater and are, therefore, a more sustainable and continuous source of Li + compared to salty brines accumulated in thousands of years. In this context, the SEArcularMINE European project aims at valorizing spent bitterns produced by the traditional and still widely employed saltworks (a schematic of the SEArcularMINE-integrated treatment chain is shown in Figure a.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, lithium recovery from aqueous sources, such as seawater, geothermal water, and salt-lake brines, has become an essential option for lithium salt production. , The solar evaporation process is the most widely used industrial method for recovering Li from brines . Several potential strategies, including adsorption, solvent extraction, and membrane-related technologies, for Li recovery from brines, have been reported to replace solar evaporation because it needs a long time to concentrate considerable amounts of Li. Adsorption is the most promising strategy for recovering Li from aqueous resources because it is more climate-friendly and more effective in an industrial application .…”
Section: Introductionmentioning
confidence: 99%